Finite-Length Analysis for Spatially Coupled LDPC Codes Based on Base Matrix - Yang Liu; Sha Sun; Yuzhi Zhang; Bin Wang (Entropy, 2023)
Spatially coupled low density parity check (SC-LDPC) are prominent candidates for future communication standards due to their “threshold saturation” properties. To evaluate the finite-length performance of SC-LDPC codes, a general and efficient finite-length analysis from the perspective of the base matrix is proposed. We analyze the evolution of the residual graphs resulting at each iteration during the decoding process based on the base matrix and then derive the expression for the error probability. To verify the effectiveness of the proposed finite-length analysis, we consider the SC-LDPC code ensembles constructed by parallelly connecting multiple chains (PC-MSC-LDPC). The analysis results show that the predicted error probabilities obtained by using the derived expression for the error probability match the simulated error probabilities. The proposed finite-length analysis provides a useful engineering tool for practical SC-LDPC code design and for analyzing the effects of the code parameters on the performances.